Acute flaccid myelitis a review of the literature - Dinov, Darina; Donowitz, Jeffrey R. (Frontiers in Neurology, 2022)
Acute flaccid myelitis (AFM) is a rare neurological disorder that first rose to national attention in 2014. This neurological disorder has a biennial presentation with every other even year being a peak year. Most patients present in childhood 5 days after a prodromal infection. Patients usually present with muscle weakness and hypo or areflexia in the summer or fall months. Clinical outcomes are variable however most patients do not improve. Currently there are no definitive prognostic factors or etiologies found. However, it is thought that enterovirus-D68 (EV-D68) could be a potential component in the pathobiology of AFM. Treatment options are limited with variable options and no consensus. Supportive therapy has been shown to be the most effective thus far. With our review of the literature, we highlight the recent growing evidence of a possible relationship between EV-D68 and AFM. Additionally, we identify the knowledge gaps in AFM with treatment and prognostic factors.